1946
DOI: 10.1021/ie50443a015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical processing of carbon blacks

Abstract: Recent publications (•>, 11, 13) concerning tic• behavior of carbon black in GR-S compounds de-S'-ribed a group of carbons as "structure carbons". These blacks arc characterized by their ability to impart smoothness to uncured stocks at normal tread stock loading, and high modulus to i•ured compounds. Such properties were attributed to structure-forming tendencies -that is, to the ability of the carbon particles to maintain a chainlike grouping (illustrated in Figure 1 as a secondary aggregate) when dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1948
1948
1949
1949

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previously this behavior was thought to involve attractive forces between separate particles and to be caused primarily by the crystal or internal structure and possibly by the surface nature as well (1). Although these forces appear to be partially responsible for chain and agglomerate formation (14), work with the stereoscopic electron microscope (17) and work on the effect of mechanical attrition on carbon particles (9) point toward structure as primarily a particle shape phenomenon. the case of Witcarb R, studies of rubber properties as a function of pigment loading showed marked increase in tear, modulus, and hardness for natural rubber and the principal synthetics.…”
mentioning
confidence: 99%
“…Previously this behavior was thought to involve attractive forces between separate particles and to be caused primarily by the crystal or internal structure and possibly by the surface nature as well (1). Although these forces appear to be partially responsible for chain and agglomerate formation (14), work with the stereoscopic electron microscope (17) and work on the effect of mechanical attrition on carbon particles (9) point toward structure as primarily a particle shape phenomenon. the case of Witcarb R, studies of rubber properties as a function of pigment loading showed marked increase in tear, modulus, and hardness for natural rubber and the principal synthetics.…”
mentioning
confidence: 99%
“…and l()t confirm this conclusion, since they show a wide variety of sizes of loose aggregates in which the ultimate particles clearly retain their individuality. It is significant that the secondary aggregates found in these detergent solutions resemble closely those found in acetylene black (9), where it Inis been shown by nitrogen adsorption experiments that disintegration of the secondary aggregates by mechanical treatment caused no significant change in particle size as determined by surface area measurements, or in the strength of the surface forces as measured by the heat of adsorption.…”
Section: Discussionmentioning
confidence: 83%
“…Since oil absorption determinations on the blacks themselves give good correlations with those properties of rubber attributed to structure (10,21) it is probable that the structure is not formed necessarily in the rubber matrix by flocculation but is present in the original black before ^compounding. Dobbin and Rossman (5) recently have demonstrated that structure blacks are fluffy and are difficult to density by direct compression or pelletization processes. These investigators were able to destroy structure characteristics by prolonged ball milling; this procedure caused higher bulk densities and a lowering of modulus in rubber.…”
Section: Structure In Carbon Blacksmentioning
confidence: 99%